Evaluating the Effectiveness of Task-Based Instruction in ESL/EFL Classrooms - Maftuna Abdurasulova (Periodica Journal, 2024)
This study examines the effectiveness of Task-Based Instruction (TBI) in English as a Second Language (ESL) and English as a Foreign Language (EFL) classrooms. TBI has been posited as a dynamic approach that enhances language proficiency by engaging learners in meaningful tasks. This research synthesizes findings from various studies to assess the impact of TBI on language skills, particularly writing and speaking. The methodology includes a meta-analysis of previous research, along with a case study conducted in Bukhara, Uzbekistan. Results indicate significant improvements in both writing and speaking skills, suggesting that TBI is a viable method for language instruction. The discussion highlights practical implications for educators and policy-makers, while the conclusion underscores the potential of TBI to transform language learning experiences.
Keywords: Task-Based Instruction; ESL; EFL